Naum, M., Linaa, J., Escribano-Ruiz, S. (eds.) (2021): Material Exchanges in Medieval and Early Modern Europe. Archaeological perspectives, Turnhout: Brepols. https://www.brepols.net/products/IS-9782503593999-1 - Casimiro, Tânia (SPAL - Revista de Prehistoria y Arqueología, 2023)
Recensión de la obra: Material Exchanges in Medieval and Early Modern Europe. Archaeological perspectives